Chemical Mechanism of MMH/NTO and Simulation in a Small Liquid Rocket Engine. Issue 12 (2nd December 2019) - Hou, Lingyun; Fu, Pengfei; Ba, Yantao
ABSTRACT: A reaction mechanism called Mech23 for gas-phase monomethylhydrazine and nitrogen tetroxide (MMH/NTO) containing 23 species and 20 reactions is developed and validated and then introduced into the numerical simulation of a small MMH/NTO liquid rocket engine. The ignition delay and equilibrium temperature predicted with Mech23 are in accordance with theoretical data within wide ranges of the MMH/NTO ratio, initial pressure, and temperature. Critical reactions are identified by the sensitivity analysis on the hypergolic ignition process of MMH/NTO mixtures. It is demonstrated that more precise predictions of thrust, specific impulse, and chamber pressure can be achieved with Mech23 than with the one-step global mechanism. Differences in the temperature distribution and gas species between the two chemical reaction mechanisms result in various performances. It is shown that the reaction mechanism plays an important role in the simulation of the engine combustion chamber.